2014
DOI: 10.3109/21681805.2014.893534
|View full text |Cite
|
Sign up to set email alerts
|

Early biochemical recurrence, urinary continence and potency outcomes following robot-assisted radical prostatectomy

Abstract: RARP provides good early BF-free survival, continence and potency recovery rates for patients eligible for NS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…In general population, potency recovery rate at one year after the surgical procedure was assessed ranging from 29.6% to 77.6% (33, 34). In the current study 6 patients (66.7%) received a nerve-sparing procedure (4 bilateral, 2 monolateral), and 5 (55.6%) achieved a potency recovery, with or without PDE5i intake, sufficient to have sexual intercourses.…”
Section: Discussionmentioning
confidence: 99%
“…In general population, potency recovery rate at one year after the surgical procedure was assessed ranging from 29.6% to 77.6% (33, 34). In the current study 6 patients (66.7%) received a nerve-sparing procedure (4 bilateral, 2 monolateral), and 5 (55.6%) achieved a potency recovery, with or without PDE5i intake, sufficient to have sexual intercourses.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary Table S1 and Figures 2 and 3 summarise the data from numerous previously published studies of RARP and UCR. 4,12,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] These studies were identified by searching for the following terms in the PubMed and Medline databases: ('nerve-sparing' OR 'preservation of the neurovascular bundles') AND ('prostatectomy' OR 'robot assisted prostatectomy') AND ('urinary incontinence' OR 'continence').…”
Section: Discussionmentioning
confidence: 99%
“…However, both meta‐analyses included both open and laparoscopic cases. Supplementary Table and Figures 2 and 3 summarise the data from numerous previously published studies of RARP and UCR 4,12,23–37 . These studies were identified by searching for the following terms in the PubMed and Medline databases: (‘nerve‐sparing’ OR ‘preservation of the neurovascular bundles’) AND (‘prostatectomy’ OR ‘robot assisted prostatectomy’) AND (‘urinary incontinence’ OR ‘continence’). Studies which did not report relative risk, hazard ratios, or odds ratios were excluded from Figures 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…живаются многие специалисты, занимающиеся хирургическим лечением РПЖ [19,20]. Иными словами, использование хотя бы 1 страховочной прокладки приравнивалось к недержанию мочи.…”
Section: рисунок 4 среднее время до восстановления функции удержанияunclassified
“…В работе Berg K.D. et al [19] у пациентов, перенесших стандартную нервосберегающую РАРП, среднее время до восстановления функции составило 6,2 мес. В исследовании Kumar A. et al [21] среднее время до полного восстановления удержания мочи составляло от 2,4 до 3,4 месяца, в зависимости от сложности хирургического вмешательства.…”
Section: рисунок 4 среднее время до восстановления функции удержанияunclassified